2022
DOI: 10.1093/cid/ciac427
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Lifetime Quality-Adjusted Life Years (QALYs) Lost Due to Syphilis Acquired in the United States in 2018

Abstract: Background The purpose of this study was to estimate the health impact of syphilis in the United States in terms of the number of quality-adjusted life years (QALYs) lost attributable to infections in 2018. Methods We developed a Markov model which simulates the natural history and management of syphilis. The model was parameterized by sex and sexual orientation (women who have sex with men, men who have sex with women[MSW], … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…On both a per-infection basis and in terms of total aggregate QALYs lost nationwide, chlamydia imposed the greatest burden, followed by gonorrhea, then trichomoniasis. Published estimates of the QALYs lost in the United States due to syphilis [ 31 ] suggest that syphilis has a higher QALY lost per infection (0.09; 95% UI, 0.03–0.19) than the 3 STIs we examined, and that syphilis is the second only to chlamydia in terms of the aggregate QALYs lost nationwide (13 349; 95% UI, 5071–31 360).…”
Section: Discussionmentioning
confidence: 81%
“…On both a per-infection basis and in terms of total aggregate QALYs lost nationwide, chlamydia imposed the greatest burden, followed by gonorrhea, then trichomoniasis. Published estimates of the QALYs lost in the United States due to syphilis [ 31 ] suggest that syphilis has a higher QALY lost per infection (0.09; 95% UI, 0.03–0.19) than the 3 STIs we examined, and that syphilis is the second only to chlamydia in terms of the aggregate QALYs lost nationwide (13 349; 95% UI, 5071–31 360).…”
Section: Discussionmentioning
confidence: 81%
“…Our estimates can be used to compare the burden of GH infection to other STIs and infections. On a per-infection basis, the estimated average number of QALYs lost due to GH (0.05 QALYs) is smaller than that due to HIV (5.80 QALYs), 58 , 59 syphilis (0.09 QALYs), 60 and gonorrhoea (among women, 0.09 QALYs), 61 while the burden of GH is higher than that of per gonorrhoea infection among men (0.0015-0.002 QALYs) 61 and per case of genital warts (0.024 QALYs). 62 , 63 , 64 At the population level, the estimated total quality-of-life burden due to GH in the US (33,100 QALYs) exceeds that of syphilis (13,300 QALYs), 60 mainly due to the higher incidence of GH.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal syphilis can cause severe harm to pregnant women, foetuses, and infants. It not only severely affects the quality of life of pregnant women [ 1 ] but also may lead to adverse pregnancy outcomes (APOs), such as preterm birth, stillbirth, and congenital syphilis [ 2 , 3 ]. Studies showed that the incidence of APOs in pregnant women infected with syphilis was significantly higher than that in pregnant women without syphilis [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%